Arabs from a Japanese Perspective: Cultural Representation and Translation - Chams, Zeina (2015)
A Master of Arts thesis in Translation and Interpreting MATI (English/Arabic/English) by Zeina Chams entitled, "Arabs from a Japanese Perspective: Cultural Representation and Translation," submitted in October 2015. Thesis advisor is Dr. Said Faiq. Soft and hard copy available.